Identification of Four Novel Loci in Asthma in European American and African American Populations - Almoguera, Berta; Vazquez, Lyam; Mentch, Frank; Connolly, John; Pacheco, Jennifer A.; Sundaresan, Agnes S.; Peissig, Peggy L.; Linneman, James G.; McCarty, Catherine A.; Crosslin, David; Carrell, David S.; Lingren, Todd; et al. (American journal of respiratory and critical care medicine, 2017)
Despite significant advances in knowledge of the genetic architecture of asthma, specific contributors to the variability in the burden between populations remain uncovered. To identify additional genetic susceptibility factors of asthma in European American and African American populations. A phenotyping algorithm mining electronic medical records was developed and validated to recruit cases with asthma and control subjects from the Electronic Medical Records and Genomics network. Genome-wide association analyses were performed in pediatric and adult asthma cases and control subjects with European American and African American ancestry followed by metaanalysis. Nominally significant results were reanalyzed conditioning on allergy status. The validation of the algorithm yielded an average of 95.8% positive predictive values for both cases and control subjects. The algorithm accrued 21,644 subjects (65.83% European American and 34.17% African American). We identified four novel population-specific associations with asthma after metaanalyses: loci 6p21.31, 9p21.2, and 10q21.3 in the European American population, and the PTGES gene in African Americans. TEK at 9p21.2, which encodes TIE2, has been shown to be involved in remodeling the airway wall in asthma, and the association remained significant after conditioning by allergy. PTGES, which encodes the prostaglandin E synthase, has also been linked to asthma, where deficient prostaglandin E synthesis has been associated with airway remodeling. This study adds to understanding of the genetic architecture of asthma in European Americans and African Americans and reinforces the need to study populations of diverse ethnic backgrounds to identify shared and unique genetic predictors of asthma.